Geo-electrical Resistivity Evaluation of Groundwater Potential at University Of Benin Ugbowo Campus, Benin-City, Edo State of Nigeria, Using the Schlumberger Array - P. Bassey; O.O. Lawrence; J. Ailego (Journal of Applied Sciences and Environmental Management, 2019)
Geo-electrical resistivity survey was conducted in part of the University of Benin, Benin-City, Ovia Northeast of Edo State, Nigeria, with a view to establishing the most dependable aquifer bearing zone and the lateral and vertical variation of subsurface lithology with distance and depth  respectively. In this study, the schlumberger electrode configuration was employed for the acquisition of VES data in the field. A total of 6 VES stations were engaged within the study area. A, H and HK resistivity curve types were identified, reflecting facies or lithological variations in the area. Three patterns of geo-electrical resistivity curves obtained using IP2WIN software can be associated with different rock formations in the study area. Dar Zarruk Parameters were tools used for aquifer characterization in determining the groundwater potential of the area and capacity bearing rating, viz: Total transverse resistance (T) and Total longitudinal conductance (S), Resistivity Contrast (RC) and Resistivity Reflection Coefficient (RRC). Results obtained shows that VES 1 (coordinate N6o 23’56.69’’, E5o 37’ 32.83’’) with four layers and an A curve type is the most potential source for groundwater compared to other VES points. It is a sandy clay layer of resistivity 198Ωm, with thickness to infinity and well confined at the top by a laterite layer. VES 1 has the highest Total Traverse Resistance 690310 Ωm2 (showing a very good transmmitivity of the layer), Resistivity Contrast (0.01) and Resistivity Reflection Coefficient (0.90), all parameters falling within good prospect for groundwater development, but has a Total Longitudinal Conductance (S) value of 0.002 mho which shows that VES 1 has a poor bearing capacity. In summary, the results of the geo-electrical resistivity survey conducted at the Vice Chancellor’s Lodge area of University of Benin using Schlumberger Array, revealed the most dependable aquifer bearing zone and the lateral and vertical variation of subsurface lithology with distance and depth respectively.